Different Evolutionary Histories in Two Subgenomic Regions of the Major Histocompatibility Complex - Gaudieri, Silvana; Kulski, Jerzy K.; Dawkins, Roger L.; Gojobori, Takashi (Genome Research, 1999)
Two subgenomic regions within the major histocompatibility complex, the alpha and beta blocks, contain members of the multicopy gene families HLA class I, human endogenous retroviral sequence (HERV-16; previously known as P5 and PERB3), hemochromatosis candidate genes (HCG) (II, IV, VIII, IX), 3.8-1, and MIC (PERB11). In this study we show that the two blocks consist of imperfect duplicated segments, which contain linked members of the different gene families. The duplication and truncation sites of the segments are associated with retroelements. The retroelement sites appear to generate the imperfect duplications, insertions/deletions, and rearrangements, most likely via homologous recombination. Although the two blocks share several characteristics, they differ in the number and orientation of the duplicated segments. On the 62.1 haplotype, the alpha block consists of at least 10 duplicated segments that predominantly contain pseudogenes and gene fragments of the HLA class I and MIC (PERB11) gene families. In contrast, the beta block has two major duplications containing the genes HLA-B and HLA-C, and MICA(PERB11.1) and MICB(PERB11.2). Given the common origin between the blocks, we reconstructed the duplication history of the segments to understand the processes involved in producing the different organization in the two blocks. We then found that the beta block contains four distinct duplications from two separate events, whereas the alpha block is characterized by multisegment duplications. We will discuss these results in relation to the genetic content of the two blocks.